Pendampingan Perancangan Balai Rukun Tetangga Untuk Memenuhi Fungsi Dasar Arsitektur Di Kawasan Hunian Masyarakat - Vijar Galax Putra Jagat Paryoko (Universitas Merdeka Surabaya, 2020)
Rukun Tetangga (RT) hall generally is a facility that provides public space for formal and informal activities by communities in a residential area. Today, function of RT hall is not only being a public social facility, but also as a regional icon, which is an effort to self-actualization of local community. Thus, the purpose of designing a hall of RT 06 at Perumahan Dosen Untag Surabaya for the community is to overcome the issues, and for the accompanying education institution is to provide indirect education about the